The impact of self‐transcendence on physical health status promotion in multiple sclerosis patients attending peer support groups. Issue 6 (December 2015) - JadidMilani, Maryam; Ashktorab, Tahereh; AbedSaeedi, Zhila; AlaviMajd, Hamid
Abstract : This study aimed to investigate the effect of self‐transcendence on the physical health of multiple sclerosis (MS) patients attending peer support groups. This study was a quasi‐experimental before‐and‐after design including 33 MS patients in three groups: 10 men in the men‐only group, 11 women in the women‐only group, and 12 men and women in the mixed group. Participants were required to attend eight weekly sessions of 2 h each. Instruments included the physical health section of the Multiple Sclerosis Quality of Life Inventory and Reed's Self‐Transcendence Scale. Peer support group attendance was found to have a significant positive effect on the physical health and self‐transcendence of MS patients when comparing average scores before and after attendance. Regression analysis showed that improvement in self‐transcendence predicted improvement in physical health. Results show the positive effects of peer support groups on self‐transcendence and physical health in MS patients, and suggest that improvement in well‐being can be gained by promoting self‐transcendence and physical health.